Pengaruh Kelengkapan Produk, Harga dan Store Atmosphere terhadap Minat Beli Konsumen pada Mr.Diy Kabupaten Toraja Utara - Peronika Peronika; Abedneigo C. Rambulangi; Stefani M. Palimbong (Universitas Kristen Indonesia Toraja, 2025)
This study aims to determine the effect of Product Assortment, Price, and Store Atmosphere on Consumer Purchase Intention at MR.DIY, North Toraja Regency. The independent variables used in this study are Product Assortment (X1), Price (X2), and Store Atmosphere (X3), while the dependent variable is Consumer Purchase Intention. The population in this study consists of consumers who have purchased products at MR.DIY. The sample in this study was selected using the accidental sampling method, with a total of 90 respondents. Data collection techniques in this study used questionnaires with a quantitative approach. The data analysis techniques used were descriptive statistical analysis and multiple regression analysis, followed by hypothesis testing using SPSS 25. Based on the results of the t-test, the product assortment variable shows a t-count value greater than the t-table value (4.574 > 1.987) with a significance level of (0.000 < 0.05). The price variable shows a t-count value greater than the t-table value (4.261 > 1.987) with a significance level of (0.000 < 0.05), while the store atmosphere variable also has a t-count value greater than the t-table value (3.857 > 1.987) with a significance level of (0.000 < 0.05). Meanwhile, the results of the F-test (simultaneous test) produce an F-count value greater than the F-table value (18.800 > 2.711) with a significance level of (0.000 < 0.05). The results of the study indicate that Product Assortment, Price, and Store Atmosphere simultaneously have a positive and significant effect on Consumer Purchase Intention at MR.DIY, North Toraja Regency.